2020
DOI: 10.1016/s1473-3099(19)30689-9
|View full text |Cite
|
Sign up to set email alerts
|

Multigenic architecture of piperaquine resistance trait in Plasmodium falciparum

Abstract: for regulatory and ethical submission. We declare no competing interests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 5 publications
1
22
0
Order By: Relevance
“…Based on the limited combinations and parasites screened as part of these initial efforts, we were able to identify combinations of PYR and PQP that have an antagonistic interactions in parasite lines with amplified plasmepsin II/III copy number variations (CNVs), a highly prevalent genotype in the Greater Mekong Subregion (11,29,30). These isolates were collected as part of a DHA-PQP efficacy study that demonstrated decreased clinical efficacy of the ACT (19) (35). Further investigation to validate and elucidate the molecular mechanism mediating the induction of an antagonistic interaction between PQP and PYR in the context of plasmepsin II/III CNV will be required, which may also aid in understanding the specific mechanism of action of these two antimalarial compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the limited combinations and parasites screened as part of these initial efforts, we were able to identify combinations of PYR and PQP that have an antagonistic interactions in parasite lines with amplified plasmepsin II/III copy number variations (CNVs), a highly prevalent genotype in the Greater Mekong Subregion (11,29,30). These isolates were collected as part of a DHA-PQP efficacy study that demonstrated decreased clinical efficacy of the ACT (19) (35). Further investigation to validate and elucidate the molecular mechanism mediating the induction of an antagonistic interaction between PQP and PYR in the context of plasmepsin II/III CNV will be required, which may also aid in understanding the specific mechanism of action of these two antimalarial compounds.…”
Section: Discussionmentioning
confidence: 99%
“…However, the overexpression of pfpm2 and pfpm3 in the 3D7 genetic background did not alter the sensitivity of P. falciparum to PPQ, suggesting that the increase in pfpm2 copy number alone is not the sole modulator of PPQ resistance [ 31 ]. Silva et al [ 32 ] have utilized gene editing and chemical inhibition to demonstrate that pfpm2 amplification contributed to PPQ resistance and that the background of the engineered parasites was necessary to gain a bimodal dose–response, in which a second peak of survival for a subset of the parasite is detected at higher PPQ concentrations [ 22 ]. It was also suggested that the initial selection of plasmepsin and pfmdr1 copy number variations developed a genetic background important for novel pfcrt mutations to emerge [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Silva et al [32] have utilized gene editing and chemical inhibition to demonstrate that pfpm2 ampli cation contributed to PPQ resistance and that the background of the engineered parasites was necessary to gain a bimodal dose-response, in which a second peak of survival for a subset of the parasite is detected at higher PPQ concentrations [22]. It was also suggested that the initial selection of plasmepsin and pfmdr1 copy number variations developed a genetic background important for novel pfcrt mutations to emerge [32].…”
Section: Introductionmentioning
confidence: 99%